(untitled) (Siddhajyoti Interdisciplinary Journal, 2020)
This paper explores English language teachers’ strategies to enhance linguistic intelligence of students studying at basic level in community schools in Nepal employing a qualitative research design. It aims to describe different techniques employed by English language teachers to develop students’ linguistic intelligence. The research participants were English language teachers teaching in community schools in Kathmandu and interviewed by using a semi-structured questionnaire to gather data to fulfil its purpose. The findings reveal that awakening students is an essential tool for enhancing linguistic intelligence along with meaningful exposure and atomistic learning provide opportunities for enhancement of linguistic intelligence at basic level.